Anesthetic implications in systemic lupus erythematosus patients posted for cesarean section: A series of five cases - Parul Jindal; Ruchi Kapoor; Gurjeet Khurana; Jaya Chaturvedi (Wolters Kluwer Medknow Publications, 2013)
Management of a parturient with systemic lupus erythematosus (SLE) requires a multidisciplinary approach. Although the ideal treatment strategy has not been formulated, certain management principles are recommended. We discuss the perioperative course and anesthetic management of five parturient with history of SLE who underwent cesarean section.